2021
DOI: 10.1146/annurev-psych-010419-050928
|View full text |Cite
|
Sign up to set email alerts
|

The Social Neuroscience of Prejudice

Abstract: The social neuroscience approach to prejudice investigates the psychology of intergroup bias by integrating models and methods of neuroscience with the social psychology of prejudice, stereotyping, and discrimination. Here, we review major contemporary lines of inquiry, including current accounts of group-based categorization; formation and updating of prejudice and stereotypes; effects of prejudice on perception, emotion, and decision making; and the self-regulation of prejudice. In each section, we discuss k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 208 publications
(232 reference statements)
5
60
0
Order By: Relevance
“…Although many contemporary theories of social cognition acknowledge the 7 importance of control, or regulatory processes (Adolphs, 2010;Amodio and Cikara, 2021;7 Frith and Frith, 2012), many key questions remain about their exact nature and neural 7 underpinnings. These include a) whether multiple forms of cognitive control contribute to 7 social cognition, b) whether these mechanisms are best understood in terms of domain-7 general processes or systems specialised for social information processing and, c) whether 7 they are ubiquitously involved or selectively engaged according to certain task demands 7 (Binney and Ramsey, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many contemporary theories of social cognition acknowledge the 7 importance of control, or regulatory processes (Adolphs, 2010;Amodio and Cikara, 2021;7 Frith and Frith, 2012), many key questions remain about their exact nature and neural 7 underpinnings. These include a) whether multiple forms of cognitive control contribute to 7 social cognition, b) whether these mechanisms are best understood in terms of domain-7 general processes or systems specialised for social information processing and, c) whether 7 they are ubiquitously involved or selectively engaged according to certain task demands 7 (Binney and Ramsey, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Frith and Frith (2012) refer to a "supervisory system" which has the characteristic features of executive control, but its functional and anatomical descriptions lack detail important for generating testable hypotheses. However, research into specific social phenomena, such as prejudice (Amodio, 2014;Amodio and Cikara, 2021) and automatic imitation (Cross et al, 2013;Darda and Ramsey, 2019) has recently begun to give the matter of cognitive control greater attention. Of particular interest has been the contribution of the domain-general multipledemand network (MDN), a set of brain areas engaged by cognitively-challenging tasks irrespective of the cognitive domain (Assem et al, 2020;Duncan, 2010;Fedorenko et al, 2013;Hugdahl et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is possible that the context-specific effects of social perception on behavior (warmth affects advantageous inequity aversion, while competence affects disadvantageous inequity aversion) could be mediated by flexible readout of the OFC signals by downstream regions 65 . Second, it remains an open question how trait representations in the mentalizing network and the OFC are constructed from semantic knowledge about social groups, possibly represented in the anterior temporal lobe [66][67][68] . Third, while we did not find evidence of trait representations in the hippocampus, a previous study reported that self-other relationships in a twodimensional ego-centric space is represented in the hippocampus 69 .…”
Section: Discussionmentioning
confidence: 99%
“…Starting in the 1980s, researchers adapted response time paradigms to study stereotype activation (e.g., [ 3 , 4 , 5 , 6 ]). More recently, various neuroscience techniques have been used to further elucidate the cognitive processes involved in stereotype activation (see reviews [ 7 , 8 , 9 ]). This line of research has revealed a great deal about stereotype activation and the conditions under which it occurs (for review, see [ 10 ]), but the vast majority has focused on only one or two social groups (e.g., racial groups, gender groups).…”
Section: Introductionmentioning
confidence: 99%